Neuro-muscular development and age-related profiling in elite youth soccer players: Conventional statistics and contributions of machine learning - Schwiete, C.; Broich, H.; Mester, J.; Wigger, U.; Wahl, P.; Behringer, M. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: From a neuromuscular perspective, soccer is characterized by the need to move ones own body mass at high speed. In addition, rapid changes of direction and quick responses to visual stimuli are needed. For these reasons, performance diagnostics often include jumping, tapping, balance and sprint tests and are supplemented by tests on changes of direction and visual information processing. However, little is known about the development of these skills in youth elite athletes. Therefore, this cross-sectional study investigated neuromuscular performance tests of elite youth soccer players across different age groups.